2015
DOI: 10.3758/s13420-015-0178-x
|View full text |Cite
|
Sign up to set email alerts
|

Human performance on random ratio and random interval schedules, performance awareness and verbal instructions

Abstract: Humans responded on multiple random-ratio (RR) random-interval (RI) schedules, and their verbalized performance awareness (PA; i.e., their ability to accurately describe what they did) was measured in three experiments. In Experiment 1, instructions informed participants that to earn points, either sometimes rapid responding and sometimes slow responding would work best (accurate instructions); rapid responding would work best (go fast instructions); spaced responding would work best (go slow instructions); or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 42 publications
4
26
0
Order By: Relevance
“…The presence of a concurrent load has been taken to be one of these steps (Reed, 2015a;Reed et al, 2018). In the absence of a concurrent load, overall human schedule performance, and within-bout responding, was not similar to that seen in nonhumans, which has also been noted in several other studies that were conducted without a concurrent task load (Bradshaw et al, 2015;Randell et al, 2009). It has been thought that such a concurrent load might act to suppress the ability to formulate verbal rules about the schedule (Reed, 2015a), which, in turn, interferes with the development of schedule control (Catania et al, 1982;Hayes et al, 1986;Lowe, 1979).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The presence of a concurrent load has been taken to be one of these steps (Reed, 2015a;Reed et al, 2018). In the absence of a concurrent load, overall human schedule performance, and within-bout responding, was not similar to that seen in nonhumans, which has also been noted in several other studies that were conducted without a concurrent task load (Bradshaw et al, 2015;Randell et al, 2009). It has been thought that such a concurrent load might act to suppress the ability to formulate verbal rules about the schedule (Reed, 2015a), which, in turn, interferes with the development of schedule control (Catania et al, 1982;Hayes et al, 1986;Lowe, 1979).…”
Section: Discussionmentioning
confidence: 92%
“…On these schedules, overall rates of response typically follow overall rates of reinforcement (Catania & Reynolds, 1968;Herrnstein, 1970;Reed et al, 2018). However, the case for humans without a concurrent task is less clear (Bradshaw et al, 2015;Hayes et al, 1986;Randell et al, 2009). Thus, while a clear relationship between decreasing overall response rates and increasing interval values, similar to that seen in nonhumans, is expected for humans with a concurrent load (Catania & Reynolds, 1968), it is harder to predict the nature of this relationship when there is no concurrent task.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent human study, Pérez and colleagues (2016) (Bradshaw, Freegard, & Reed, 2015;Reed, 2001) (Blanco, Matute, & Vadillo, 2013;Dickinson, Shanks, & Evenden, 1984;Hammond & Paynter, 1983;Wasserman, Chatlosh, & Neunaber, 1983) or variations of this metric (Cheng, 1997;Novick & Cheng, 2004). The most plausible explanation for Reed's (2001) results is that participants attribute causal control in line with the correlational properties of the schedules, independently of reward rate or reward probability.…”
Section: Discussionmentioning
confidence: 99%
“…The idealized versions of these two schedules are the random ratio (RR) and random interval (RI) schedules, where the probability of reinforcement per response-in the ratio case-and the probability of a reinforcer becoming available per second-in the interval case-are given by binomial (or geometric) distribution (see Cardinal & Aitken, 2010). Using a variety of species and target instrumental responses, a wealth of evidence has shown that ratio schedules support higher response rates than interval schedules despite the probability of reinforcement or the reinforcement rate being matched (Bradshaw, Freegard, & Reed, 2015;Bradshaw & Reed, 2012;Catania, Matthews, Silverman, & Yohalem, 1977;Dawson & Dickinson, 1990;Peele, Casey, & Silberberg, 1984;Reed, 2001aReed, , 2001cZuriff, 1970). Mackintosh (1974) was fully aware of the ratio-interval contrast and discussed whether ratio and interval schedules differentially reinforce divergent response rates-that is, whether different response rates bring about different reinforcement probabilities on ratio and interval schedules.…”
mentioning
confidence: 99%